Timing of Emergency Postpartum Hospital Visits in the Fourth Trimester - Rodriguez, Aldeboran N.; Patel, Shivani; Macias, Devin; Morgan, Jamie; Kraus, Alexandria; Spong, Catherine Y. (American Journal of Perinatology, 2020)
Objective The concept of the “fourth trimester” emphasizes the importance of individualized postpartum follow-up. Women seek care for urgent issues during this critical time period. Our objective was to evaluate trends in presenting complaints and admissions in an emergency setting over the first 42 days following delivery.Study Design Postpartum hospital encounters within 42 days of delivery at our institution from 2015 to 2019 were studied. Demographic information, delivery route, and emergent hospital encounter details were obtained from the electronic medical record. The postpartum encounters were analyzed by week of presentation. Statistical analysis included Student's t-test and Mantel–Haenszel test with p <0.05 considered significant.Results Of the 8,589 deliveries, 491 (5.7%) were complicated by an emergent hospital presentation within 42 days of delivery resulting in 576 hospital encounters. 35.9% of these visits occurred in the first week and 75.5% occurred within the first 3 weeks. Women presenting to the hospital were more commonly African American, higher body mass index, and delivered via cesarean. The most common chief complaints were fever, headache, abdominal pain, vaginal bleeding, hypertension, and wound concerns with temporal trends noted. 72% of admissions occur within 14 days of delivery and drop dramatically thereafter (p = 0.001). The most common diagnoses were hypertension/preeclampsia with severe features, vaginal bleeding/delayed postpartum hemorrhage, and wound infection.Conclusion We observed important trends in presenting complaints and admission diagnoses of emergency postpartum visits in the first 42 days. The majority of hospital visits and admissions occur within the first 2 weeks postpartum. Understanding maternal conditions and reasons for accessing care through an emergency setting allows for tailoring of routine postpartum follow-up.Key Points
Keywords: postpartum; fourth trimester; emergency room; readmission